2020
DOI: 10.1530/rep-19-0355
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the contraceptive effects of ulipristal acetate

Abstract: The use of emergency contraception (EC) methods is increasing worldwide as it constitutes an effective way to prevent unplanned pregnancy after unprotected sexual intercourse. During the last decade, ulipristal acetate (UPA), a selective progesterone receptor modulator, has emerged as the most effective EC pill, and it is now recommended as first-line hormonal treatment for EC in several countries. Its principal mechanism of action involves inhibition or delay of follicular rupture, but only when administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The most effective method is a copper intrauterine device (Cu-IUD), which can be left in place as ongoing contraception afterwards. Selective progesterone receptor modulators such as ulipristal acetate are among the most effective emergency contraceptive pills (ECPs) available [ 25 ]. ECPs containing levonorgestrel are another method of EC.…”
Section: Main Textmentioning
confidence: 99%
“…The most effective method is a copper intrauterine device (Cu-IUD), which can be left in place as ongoing contraception afterwards. Selective progesterone receptor modulators such as ulipristal acetate are among the most effective emergency contraceptive pills (ECPs) available [ 25 ]. ECPs containing levonorgestrel are another method of EC.…”
Section: Main Textmentioning
confidence: 99%
“…In spite of this, the authors conclude verbatim that "the mechanism of action of UPA when used as an EC does not disrupt the implantation process", and always refer to implantation in the abstract's Study Question, Summary Answer and Conclusions. This message seems intentionally deceiving, It should be clear, at this point, that the prevalent MOA of ellaOne ® is linked to its antiprogestational effect on the endometrium and not to any effect on the process of ovulation 60 . All this information, however, was already evident when ellaOne ® was introduced into the market as an anti-ovulatory drug 31 : the papers describing its effects in women are the same discussed above.…”
Section: Ellaone ® and Endometriummentioning
confidence: 99%
“…5.Ulipristal acetate, brand name ellaOne, is a different EC that recent studies have shown has high suggestibility of post-fertilization effects by decreasing endometrium suitability for implantation; therefore, this paper will focus solely on LVG (Munuce et al 2020; Lira-Albarrán et al 2017). …”
mentioning
confidence: 99%